Development of Canva website-based learning media on the topic of organism classification in class X - Devy Widyasari; T. Titin; Eko Sri Wahyuni (University of Muhammadiyah Malang, 2025)
Learning media is one of the important aspects of the learning process. Current technological advances make learning media innovative and allow it to face adjustments, one of which is using Canva website-based media. This research aims to develop Canva website-based learning media on the topic of organism classification and to determine the results of validation and reliability. The method used is R&D with the Borg & Gall model, carried out in five stages. The research instruments used were interview sheets and validation sheets. Data analysis of validation results was calculated using Aiken's V formula. Media validation was conducted by two lecturers of Biology Education FKIP UNTAN and three biology teachers of class X from SMAN 1 Sungai Raya, SMA Kemala Bhayangkari I, and SMA Taruna Bumi Khatulistiwa. Meanwhile, the reliability test used the Intraclass Correlation Coefficient. The results showed that the Canva website-based media validation obtained a value of 0.89, including the valid category. In addition, the reliability results obtained a value of 0.754, including the excellent reliability category. These results indicate that this Canva website-based media is valid and feasible for learning the organism classification topic in class X.